2021
DOI: 10.21203/rs.3.rs-366255/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IFN-γ mediated signaling improves fungal clearance in experimental pulmonary mucormycosis.

Abstract: We established three immunocompetent murine models of pulmonary mucormycosis to determine the involvement of the adaptive immune response in host resistance in pulmonary mucormycosis, a rapidly fatal disease caused mainly by Rhizopus spp. Immunocompetent BALB/c, C57BL/6, and Swiss mice were inoculated with R. oryzae via the intratracheal route. The inoculation resulted in an angioinvasive infection that spread to the brain, spleen, kidney, and liver. After 7 and 30 days of R. oryzae infection, C57BL/6 and BALB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In the present study, BALB/c and Swiss mice strains showed more and less resistance, respectively, against in vivo R. oryzae infection, as previously reported (30,31). The course of infection was characterized by similar fungal load on day 7 for both mouse strain, followed by a decreased fungal load on day 30, that was more expressive in BALB/c mice (Fig 2A).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, BALB/c and Swiss mice strains showed more and less resistance, respectively, against in vivo R. oryzae infection, as previously reported (30,31). The course of infection was characterized by similar fungal load on day 7 for both mouse strain, followed by a decreased fungal load on day 30, that was more expressive in BALB/c mice (Fig 2A).…”
Section: Resultssupporting
confidence: 90%
“…Generally, high levels of ROS production by macrophages are linked to intracellular events, including the activation of transcription factors such as NFκB (71), and induction of mitogenesis (72). In addition, in vitro , and in vivo studies already showed that R. oryzae could trigger a Th-17 response mediated by high amounts of IL-23 by dendritic cells (73), and also the association of high levels of IL-17 and IFN-γ with better R. oryzae elimination by immunocompetent BALB/c and C57BL/6 mice (30,31). Considering the studies above and the evidence found here, we hypothesized that adaptive immune responses developed by BALB/c mice were essential to enhance the fungicidal activity of peritoneal macrophages and efficiently kill R. oryzae .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations